2013
DOI: 10.2190/ec.49.4.c
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Preschool Teachers' Technological Pedagogical Content Knowledge of Educational Games

Abstract: Current technological pedagogical content knowledge (TPACK) studies are inclined to treat technology in a general manner, an approach which may not be able to provide adequate guidelines to improve teacher preparation and professional development when teaching with games. This study developed two new questionnaires, namely the Technological Pedagogical Content Knowledge-Games (TPACK-G) survey to investigate 352 preschool teachers' confidence in their TPACK-G, and the Acceptance of Digital Game-Based Learning (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 39 publications
(61 reference statements)
4
39
0
Order By: Relevance
“…In the study of Praet and Desoete (2014) examining 132 kindergarteners' arithmetic skills, the results show that in comparison with the children who did not play games, those who played games tended to have better performance on mental arithmetic and number knowledge in the immediate and delayed tests. Meanwhile, (Hsu et al 2013) also found that preschoolers of age six could construct scientific understanding about light and shadow after the treatment of game-based learning.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the study of Praet and Desoete (2014) examining 132 kindergarteners' arithmetic skills, the results show that in comparison with the children who did not play games, those who played games tended to have better performance on mental arithmetic and number knowledge in the immediate and delayed tests. Meanwhile, (Hsu et al 2013) also found that preschoolers of age six could construct scientific understanding about light and shadow after the treatment of game-based learning.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the feedback given, they can also modify their strategies, repeatedly improve the game-playing outcomes, and gain enjoyment from it (Chang et al 2010). Most of all, games have the potential of promoting conceptual understanding and process skills (Barab et al 2010;Hsu et al 2013;Praet and Desoete 2014). In the study of Praet and Desoete (2014) examining 132 kindergarteners' arithmetic skills, the results show that in comparison with the children who did not play games, those who played games tended to have better performance on mental arithmetic and number knowledge in the immediate and delayed tests.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies about the use of TPACK in teacher education have increased in recent years to measure TPACK Archambault and Barnett, 2010;Koh et al, 2010;Sahin, 2011;Fisser et al, 2015;Kartal and Afacan, 2017;Drummond and Sweeney, 2017), to examine the information communication technologies (ICT) and TPACK integration (Öztürk, 2012;Chai et al, 2014;Yurdakul and Çoklar, 2014;Tondeur et al, 2015;Gür and Karamete, 2015;Ersoy et al, 2016;Kihoza et al, 2016;Koh et al, 2017;Kontkanen et al, 2017), for exploring teachers' technological pedagogical content knowledge (Hsu et al, 2013;Delen et al, 2015;Dong et al, 2015;Boschman et al, 2015;Phillips, 2017;Turgut, 2017), to examine TPACK and teachers' self-efficacies (Kazu and Erten, 2014;Kenar et al, 2015;Saudelli and Ciampa, 2016;Blonder and Rap, 2017), to determine TPACK and needs of Twenty-First-Century Education (Mishra, Koehler and Henriksen, 2010;Koh et al, 2015;Cherner and Smith, 2017).…”
Section: Technological Pedagogical and Content Knowledge (Tpck)mentioning
confidence: 99%